Thank God for the greatest country on earth: white supremacy, vigilantes, and survivalists in the struggle to define the American nation. Issue 3 (3rd July 2018) - Crockford, Susannah
ABSTRACT: The election of Donald Trump in 2016 has been identified by observers as the outcome of a wave of nationalist populism in the U.S.A. This article interrogates the meaning of nationalist populism in contemporary American culture with respect to far-right extremism. White supremacists, border vigilantes, and survivalists are forms of far-right extremism that illuminate the nationalist populism of mainstream right-wing American politics. In particular, the politics of religion of the far-right are examined as a microcosm of the Christian right. Using ethnographic data collected over a period of four years in northern Arizona, the politics of religion of one particular family renders anthropological nuance to broad categorisations of the 'white working class' and its importance in the election of Donald Trump. How this family variously constructs 'God' as a central value of the American nation indicates the ongoing and potentially dangerous struggles of nationalism in the current political climate.